Os modos de subjetivação do indivíduo através da sexualidade segundo Foucault - Carlos, Cledson de Souza (2017)
The present work, based on Michel Foucault, is a theoretical-bibliographical research about the ways of the individual subjectivation through the sexuality, which is present in the greek aesthetics of existence and in the modern sexuality device. We proposed to study the following problem: how the power acts on the individual in the process of subjectivation through the sexuality. To analyze the contemporary sexuality, Foucault gives distinction to two types of Power: the Sovereign Power and the Biopower. In analyzing the sexuality according to the Sovereign Power, we noted mistakenly that the main effect of the power is the suppression. Because of that misunderstanding, Foucault deconstructs that kind of insufficient analysis, criticizing the repressive theory and demonstrating that the main acting of the power in the sexuality in the contemporaneity is through the sexuality device stimulating its manifestation and the sexual discursive. However Foucault shows that the sexuality can be lived distinctly, so it presents another way of subjectivation, studying as the classic greek developed their sexuality as aesthetics of existence. Finally we noted that the sexuality is historically built and it has not a natural datum, so the contemporary individual has the possibility to elaborate from itself a free life and creative.